Successful perioperative preparation of a child with autism spectrum disorder in collaboration with his school for special needs education: a case report - Arai, Yuto; Okanishi, Tohru; Nakamura, Yuko; Maegaki, Yoshihiro (Frontiers in Psychiatry, 2024)
Introduction: The incidence of autism spectrum disorder (ASD) in children is greater than 1%. Children with ASD show an increased rate of hospital contact for several reasons. Perioperative preparation for children with ASD can be challenging; therefore, obtaining information from patients’ families prior to surgery is important. However, no previous reports have described the collection of information from educational facilities. Case report: A 12-year-old male patient with ASD was referred for surgery for traumatic dislocation of the left knee joint. Before admission, we obtained valuable information from his parents regarding expected behavioral problems and coping strategies during hospitalization and from his teachers at his school for special needs education. In particular, the information obtained from teachers was specific and practical. Consequently, we could effectively conduct perioperative management based on his specific autistic characteristics. Conclusion: We report a pediatric case of ASD in which favorable perioperative management was successfully achieved by collecting information before admission from family members as well as teachers at the patient’s school for special needs education. This management may help in future hospital admissions for children with autism.